Survival Following Rectal Impalement through the Pelvic, Abdominal, and Thoracic Cavities: A Case Report - Michael Moncure; Jared A. Konie; Adam B. Kretzer; Peter J. DiPasco; Carla C. Braxton (Case Reports in Medicine)
Impalement injuries are a unique form of penetrating trauma and are typically associated with a fall onto the object (Steele, 2006). We present the case of a 45-year-old man who reportedly slipped in his bathtub and fell onto a broomstick. Radiographic examination revealed a slender mass extending from his rectum to the right side of his neck. A review of English literature suggests that this is the second reported case in the last 100 years describing the successful management of an impalement injury traversing the pelvic, abdominal, and thoracic cavities. The management of this case is described.